PROJECT: SCREENPLAY GOING HOME - Katarina Septi; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2017)
This paper explained the process and the result of my final project which is a screenplay entitled Going Home. The screenplay is about Dahlia, a thirteen-year-old girl who was born and grew up in Australia. Then, she has to return to Jakarta, Indonesia and continue her education in Indonesia. She has an assignment about history of Indonesia. She needs to write one of heroic history of Indonesia with her own words and write her reflection about it. Once, she goes to Surabaya for a holiday and stays at Majapahit Hotel Surabaya. In the hotel, she experiences the past life about several historical moments by going back and forth to a past life and present life. After experiencing it, she can feel and understand the spirit of the Indonesian revolutionary heroes. She respects Indonesia heroes more. Also, she can encourage her friends to love Indonesia better and to blend in diverse group of ethnics as strong and one Indonesian who support to improve Indonesia. I would like to show that young generations are now lack the spirit to build their country. They forget to become one; One Land, One Nation, One Language. This creative work focuses on how history of Indonesia can help young generations to gain the spirit of Indonesian revolutionary heroes to love and improve Indonesia. To put this issue into a form of entertainment, I decided to make a screenplay which type of genre is adventure fantasy.